UV and Visible light photodegradation of methylene blue with graphene decorated titanium dioxide - M A Acosta-Esparza; L P Rivera; A Pérez-Centeno; A Zamudio-Ojeda; Daniel Ramírez González; A Chávez-Chávez; M A Santana-Aranda; J Santos-Cruz; J G Quiñones-Galván (Materials Research Express, 2020)
Photocatalytic degradation of methylene blue by graphene decorated titanium dioxide (TiO _2 ) powders heated at different temperatures was analyzed. The powders were prepared by mixing TiO _2 with graphene prepared by the modified Hummers method. A thermal treatment was applied to mixed and pure TiO _2 powders with the aim of analyze their structural dependence on temperature, and consistently their photocatalytic degradation effect on methylene blue solutions exposed to UV and visible radiation. Structural characterization of the powders was carried out by x-ray diffraction and Raman spectroscopy. When irradiated with UV, the mixed powders showed as high as 87% photocatalytic degradation, while the pure TiO _2 reached values of 59%. For visible radiation, as it is expected, the pure TiO _2 showed no activity, while the mixture presented degradation of 40%.